Space as a Basic Concept of Geography: A New Journey into the History of Geography - Wardenga, Ute (Journal of Geography Education, 2024)
This paper suggests how the spatial concepts applied in geography education can be reinterpreted and reconfigured. For this purpose, it starts from the hypothesis, which is very well proven in the history of geography, that the discipline has always been a response to globalization processes. The resulting concepts build on each other and lead to specific forms of geographical literacy, namely (1) regional reography, which works with the concept of inventoried and scaled spaces; (2) landscape geography, which develops the concept of shaped spaces; (3) functionalist geography, which applies models of structured spaces, and (4) geographies of places, which focus on dynamized and interwoven spaces.